Renal Barocrinology: The Interface between Obesity and Kidney Health - Sourabh Sharma; Sabine Karam; Nitin Kapoor; Sanjay Kalra (Journal of the Pakistan Medical Association, 2025)
Obesity is been acknowledged to be a major risk factor for chronic kidney disease (CKD), contributing to both its onset and progression. Over past few decades, the obesity epidemic has lead to an increased incidence of obesityrelated nephropathy, characterised by glomerular hyperfiltration, hypertrophy, and progressive glomerulosclerosis. This review highlights the need for multidisciplinary action to prevent and manage obesityrelated nephropathy. We reiterate the current necessity of routine kidney function screening in people with obesity. We also propose an integrated concept of Renal Barocrinology. This will focus on early screening and preventive strategies, mitigating long-term burden of CKD and its complications, and improving patient outcomes through a collaborative approach. Keywords: Obesity, Chronic Kidney Disease, Hyperfiltration, Proteinuria, Early Screening, Renal Barocrinology